Why education is not helping the poor. Findings from Uganda. (October 2018) - Datzberger, Simone
Highlights: Education policies, reforms and governance failed to respond to the multidimensional needs of the poor. Assimilative models are not responsive to the root causes of poverty to really affect social transformation and change. There is a need for transformative policies that are cross-sectoral and not just designed for the education sector alone. The political economy context of a country cannot be detached from education sector reforms. The focus on economic empowerment through education sidelines the role of enhancing the political agency of the poor. Abstract: Education emerged as a nearly uncontested development strategy to tackle several forms of social, political, economic and geographic inequalities in low- and middle-income countries. When it comes to the case of Uganda, the country represents a striking paradox. Significant investments and policy reforms in education (such as Universal Primary and Secondary Education) since 1997, did not translate into the expected results with regards to poverty reduction through human capital investment. Progress in poverty alleviation is not only stagnant but the role of education therein can be described as 'modest' at best. Against this backdrop, this article assesses the following research question: Why did Uganda's investments and policy reforms in education not uplift the poor? In examining the issue, this article introduces a theoretical framework that contrasts assimilative with transformative approaches in poverty alleviation through education. A rigorous review of Uganda's education sector plans revealed that current strategies to reduce poverty revolve around a strong assimilation-based development agenda, thereby focusing on three main areas of intervention: (a) increased access to education and retention; (b) improved quality of education; and (c) employment generation through education. The article finds that these assimilative approaches do not have an impact on the political, economic and social structures that cause poverty in the first place. Hence, it concludes that assimilative models in education are highly dependent on transformative approaches. Concretely, change cannot emerge only at the very grassroots level, i.e. through educating society at large, but also has to arise from the systemic level, i.e. government institutions at the local, national and global levels. Methodologically, the analysis draws on qualitative data that was collected in the course of two extensive field research stays in 2015 and 2017. In addition, quantitative data in the form of statistical abstracts inform the analysis.